2012
DOI: 10.3389/fnsys.2012.00059
|View full text |Cite
|
Sign up to set email alerts
|

Insights into multimodal imaging classification of ADHD

Abstract: Attention deficit hyperactivity disorder (ADHD) currently is diagnosed in children by clinicians via subjective ADHD-specific behavioral instruments and by reports from the parents and teachers. Considering its high prevalence and large economic and societal costs, a quantitative tool that aids in diagnosis by characterizing underlying neurobiology would be extremely valuable. This provided motivation for the ADHD-200 machine learning (ML) competition, a multisite collaborative effort to investigate imaging cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
106
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(118 citation statements)
references
References 84 publications
3
106
2
Order By: Relevance
“…The methods were implemented in a similar fashion as Colby et al (2012). We applied linear support vector machine recursive feature elimination (SVM-RFE; Guyon et al, 2002) in order to obtain a ranked list of features that best distinguished the 85 epilepsy patients with defined MTS from the 84 without.…”
Section: Machine Learning Methods and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The methods were implemented in a similar fashion as Colby et al (2012). We applied linear support vector machine recursive feature elimination (SVM-RFE; Guyon et al, 2002) in order to obtain a ranked list of features that best distinguished the 85 epilepsy patients with defined MTS from the 84 without.…”
Section: Machine Learning Methods and Analysismentioning
confidence: 99%
“…Support vector machines (SVM) are a class of machine learning algorithms that are well suited for neuroimaging data as they are fast, flexible and can be readily automated. They have been studied extensively in computer science and have been applied to neuroimaging data from a variety of neurological diseases including Alzheimer's disease (Klöppel et al, 2008), autism spectrum disorder (Ecker et al, 2010) and ADHD (Colby et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…From a neuroimaging viewpoint, compelling evidence points to rather large-scale abnormalities in network organization in ADHD (Sergeant et al, 2006;Konrad and Eickhoff, 2010;Cao et al, 2013), affecting both functional (Cocchi et al, 2012;Colby et al, 2012;Fair et al, 2012;Tomasi and Volkow, 2012;Cao et al, 2013;Di Martino et al, 2013) and structural (Cao et al, 2013;Hong et al, 2014) connectivity. Moreover, an abnormal hemispheric asymmetry of brain structure and function was also consistently reported in ADHD (Dennis and Thompson, 2013;Shang et al, 2013;Cao et al, 2014;Hale et al, 2014Hale et al, , 2015Keune et al, 2015;Silk et al, 2015), suggesting a possible neurodevelopmental scenario for this disorder.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the intensity of activation network yielded clusters with fair precision, which is close to other studies that reported precision values around 75% in: epilepsy (J. Zhang et al, 2012), attention-deficit hyperactivity disorder (Colby, 2012;Dai et al, 2012), autism (Anderson et al, 2011), Alzheimer's disease J. Wang et al, 2013b), schizophrenia (Bassett et al, 2012), and unipolar or severe depression (Lord et al, 2012;Zeng et al, 2012).…”
Section: Discussionsupporting
confidence: 61%